Topological arrangement of coronal segments in human callosal fibers in vivo tractography - Zhang, Hui; Feng, Yuan; Li, Weiguang; Liang, Xili; Huang, Guanglong; Qi, Songtao (Frontiers in Neuroanatomy, 2023)
The topography of human callosal fibers in the midsagittal corpus callosum (mid-CC), in terms of cortical termination, is inconsistent in the literature. Despite being a high-profile and controversial topic, heterotopic callosal bundles (HeCBs) have not been studied from a whole-brain perspective. Here, we used multi-modal magnetic resonance imaging data from Human Connectome Project Development to explore these two topographic aspects by combining whole-brain tractography based on multi-shell multi-tissue constrained spherical deconvolution, the post-tractography reducing-false-positive-streamline algorithm of Convex Optimization Modeling for Microstructure Informed Tractography 2, and the new cortex parcellation atlas of Human Connectome Project multi-modal parcellation, version 1.0. We proposed that the callosal streamlines would demonstrate a topological arrangement of coronal segments arranged from anterior to posterior, with each perpendicular to the long axis of the mid-CC following its natural curvature, and the adjacent segments overlapping one another owing to the existence of HeCBs. We found that the cortices connected by the coronal segments, from anterior to posterior, corresponded exactly to the cortices from anterior to posterior in the flattened cortical surfaces of this atlas, indicating the original relative positions of the neocortex before curling and flipping during brain evolution. For each cortical area defined by this atlas, the sum strength of the HeCBs was far greater than that of the homotopic callosal bundle. Our findings on the topography of the whole CC would help in further understanding the network between the bilateral hemispheres and preventing disconnection syndromes in clinical settings.